Mechanical Design and Numerical Analysis of a New Front Wing for a Formula One Vehicle - Aldo Saul Laguna-Canales; Guillermo Urriolagoitia-Sosa; Beatriz Romero-Ángeles; Miguel Martinez-Mondragon; Miguel Angel García-Laguna; Martin Ivan Correa-Corona; Daniel Maya-Anaya; Guillermo Manuel Urriolagoitia-Calderón (Fluids, 2023)
In motorsports, the correct design of every device that constitutes a vehicle is a significant task for engineers because the car’s efficiency on the track depends on making it competitive. However, the physical integrity of the pilot is also at stake, since a bad vehicle design can cause serious mishaps. To achieve the correct development of a front wing for a single-seater vehicle, it is necessary to adequately simulate the forces that are generated on a car to evaluate its performance, which depends on the aerodynamic forces of the front wing that are present due to its geometry. This work provided a new design and evaluation through the numerical analysis of three new front wings for single-seater vehicles that comply with the regulations issued by the International Automobile Federation (FIA) for the 2022 season. Additionally, a 3D-printed front wing prototype was developed to be evaluated in an experimental study to corroborate the results obtained through computer simulations. A wind tunnel experiment test was performed to validate the numerically simulated data. Also, we developed a numerical simulation and characterization of three front wings already used in Formula One from a previous season (the end of the 2021 season). This work defined how these devices perform, and in the same way, it identified how their evolution over time has provided them with substantial benefits and greater efficiency. All the numerical simulations were carried out by applying the Finite Volume Method, allowing us to obtain the values of the aerodynamic forces that act on the front wing. Also, it was possible to establish a comparison between the three newly designed proposals from the most aerodynamic advantages to produce a prototype and perform an experimental test. The results of the experimental test showed similarity to those of the numerical analyses, making it clear that the methodology followed during the development of the work was correct. In addition, the mechanical designs carried out to develop the front wing can be considered ideal, because the results showed that the front wing could be competitive, and applying it caused a downforce to be favored that prevented the car from being thrown off the track. Additionally, the results indicate this is an effective proposal for use in a single-seater vehicle and that the design methodology delivers optimal results.